A pragmatic continuum level model for the prediction of the onset of keyholing in laser powder bed fusion - Johann Sienz (International Journal of Advanced Manufacturing Technology, 2019)
Laser powder bed fusion (L-PBF) is a complex process involving a range of multi-scale and multi-physical phenomena. There has been much research involved in creating numerical models of this process using both high and low fidelity modelling approaches where various approximations are made. Generally, to model single lines within the process to predict melt pool geometry and mode, high fidelity computationally intensive models are used which, for industrial purposes, may not be suitable. The model proposed in this work uses a pragmatic continuum level methodology with an ablation limiting approach at the mesoscale coupled with measured thermophysical properties. This model is compared with single line experiments over a range of input parameters using a modulated yttrium fibre laser with varying power and line speeds for a fixed powder layer thickness. A good trend is found between the predicted and measured width and depth of the tracks for 316L stainless steel where the transition into keyhole mode welds was predicted within 13% of experiments. The work presented highlights that pragmatic reduced physics-based modelling can accurately capture weld geometry which could be applied to more practical based uses in the L-PBF process.